LITERATURE STUDY: IMPROVING CHILDREN’S NATURALIST INTELLIGENCE THROUGH FIELD TRIP METHODS - Nadia Ayu Martasari; Alya Insan Nabilah; Conny Dian Sumadi (maktab: Jurnal Pendidikan dan Teknologi, 2022)
According to Gardner, one type of intelligence is naturalist intelligence. Someone with this intelligence has the potential to care about the environment. Therefore, this intelligence is very important to be developed. One method which in previous studies has been proven to be able to develop naturalist intelligence is the field trip method. This study aims to find out how the environmentally friendly field trip method can increase naturalistic intelligence in children. This research belongs to the literature study research. Sources of data in this study come from journals, books, or scientific works that are still related to naturalistic intelligence and learning methods of eco-friendly field trips. The data that has been collected is then analyzed using descriptive methods from the sources that have been collected. The results of this study state that the environmentally friendly field trip method can be used to increase naturalistic intelligence in children by doing this activity, children will be more familiar with the environment and will foster care for the environment. The role of teachers in schools and parents is also very influential in increasing naturalistic intelligence in children